PERAN PENDIDIKAN KEWARGANEGARAAN BERBASIS NILAI-NILAI PANCASILA DALAM MENCEGAH ISU RADIKALISME - Esra Julita Br PA; Roselli Lumbansiantar; Saparutdin Brutu; Riska Marpaung; Abigael Siallagan; Putri Andini; Fazli Rachman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Citizenship education is very important to build national character based on Pancasila values, especially in overcoming radicalism. Education based on Pancasila values ​​is very important to foster national insight, an attitude of tolerance and a sense of togetherness in society because radicalism that develops in society can threaten national unity. The role of citizenship education in preventing radicalism is examined in this research. The research results show that internalizing Pancasila values ​​in the learning process can help prevent radical ideology from spreading. By teaching values ​​such as unity, humanity and social justice, students will better understand the importance of maintaining the integrity of the country. In this research, the literature study method was used to investigate various sources related to radicalism and citizenship education. Apart from that, this research also wants to explain how citizenship education based on Pancasila values ​​helps students understand the importance of tolerance, pluralism and national awareness amidst the threat of radical ideology. Citizenship education is considered to be able to instill inclusive and moderate national values ​​to prevent radicalism from spreading in society. The author also wants to know how effective citizenship education based on Pancasila values ​​is in forming citizens who are aware of radicalism and have attitudes and behavior that support unity. and national unity.